2022
DOI: 10.3390/ijerph191610173
|View full text |Cite
|
Sign up to set email alerts
|

TTN Variants Are Associated with Physical Performance and Provide Potential Markers for Sport-Related Phenotypes

Abstract: TTN encodes the third myofilament, titin, which plays structural, mechanical, regulatory, and developmental roles in sarcomeres. The aim of this research was to determine the interaction between novel and previously described TTN variants and athletic performance, as well as competition level, in Caucasians. Firstly, 100 athletes and 47 controls were recruited, and whole-genome sequencing was performed. Secondly, 348 athletes (108 endurance, 100 sprint/power, 140 mixed-sport athletes) and 403 volunteers were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…It has been reported that specific polymorphisms in these genes may be associated with the type of sport parameters affected and the performance of athletes. Similar association studies have been conducted and reported in different populations and for diverse genes and sports disciplines [1,[11][12][13][14]. Considering this information, the impact of genetic factors on athletic performance holds significant importance in the development of training programs and in maximizing athletes' physical and physiological potential.…”
Section: Introductionsupporting
confidence: 66%
“…It has been reported that specific polymorphisms in these genes may be associated with the type of sport parameters affected and the performance of athletes. Similar association studies have been conducted and reported in different populations and for diverse genes and sports disciplines [1,[11][12][13][14]. Considering this information, the impact of genetic factors on athletic performance holds significant importance in the development of training programs and in maximizing athletes' physical and physiological potential.…”
Section: Introductionsupporting
confidence: 66%